TBX21 knockdown attenuates neuroinflammation induced by intracerebral hemorrhage via the SIRT1-WDR5-H3K4me3 axis - Zou, Zhichao; Liu, Zhi; Zhang, Zhanwei; Li, Xiaojing (Brain research bulletin, 2025)
Neuroinflammation is a key contributor to the development of secondary brain injury (SBI) following intracerebral hemorrhage (ICH). This study aimed to elucidate the role and underlying mechanisms of T-box transcription factor 21 (TBX21), a known regulator of type I inflammatory responses, in ICH-induced neuroinflammation. An in vitro oxygen-glucose deprivation (OGD) model using BV2 microglia and an in vivo autologous blood injection-induced ICH rat model were used to modulate TBX21 and sirtuin 1 (SIRT1) expression. The results showed that TBX21 knockdown significantly suppressed the OGD-induced release of pro-inflammatory cytokines (IL-1β, IL-6, TNF-α), decreased levels of the oxidative stress marker malondialdehyde (MDA), and restored the activities of antioxidant enzymes superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px). In addition, TBX21 knockdown reversed the OGD-induced upregulation of TBX21, WDR5, H3K4me3, cyclooxygenase-2 (COX2), and inducible nitric oxide synthase (iNOS), while enhancing SIRT1 expression. Mechanistically, TBX21 could directly bind to the promoter region of SIRT1 and suppress its transcription, and the protective effects of TBX21 knockdown were abolished by SIRT1 knockdown. In the ICH rat model, TBX21 knockdown or SIRT1 overexpression led to improvements in neurological severity scores, reductions in hematoma volume, and restoration of tight junction protein expression (occludin, claudin-3, and ZO-1). Collectively, these findings indicate that TBX21 promotes post-ICH neuroinflammation by repressing SIRT1, thereby enhancing WDR5-mediated H3K4me3 epigenetic modifications. TBX21 may therefore serve as a promising therapeutic target for mitigating SBI after ICH. •TBX21 knockdown reduces OGD-induced neuroinflammation in BV2 cells.•TBX21 binds SIRT1 promoter, suppressing its expression in OGD models.•SIRT1 overexpression reduces neuroinflammation via WDR5-H3K4me3 inhibition.•TBX21 knockdown reduces ICH injury via SIRT1-mediated WDR5-H3K4me3 suppression.